University of the Philippines Mindanao course scheduler faculty and room scheduling subsystem - San Pablo, Karen Rachel Jabagat (2011)
With the automation of more and more processes in the university, the idea of bringing the automation down to the departmental level became a more promising endeavor. With the use of a MySQL database server, this system was built to facilitate the assigning of courses to faculty and rooms. It has with it a user-friendly interface that will not leave the user (the program coordinator of each department) guessing on what a link or button does. It was also designed with modules that make the scheduling process more efficient. The faculty and room scheduling modules facilitate the scheduling of the department's faculty and rooms, respectively and the checking of conflict within the submitted schedule or between it and schedule and the schedule already existing in the database. Accordingly, when conflicts are detected, the user is informed about them. When the user wants to revise a saved schedule, there is also the schedule revision module, which updates the schedule of a faculty/room whenever the user edits it. The faulty and room management modules allow the adding, editing, deleting and unloading of faculty and rooms, while the list generator module generates a faculty list view of the already saved schedules. The system can be made more efficient by employing AJAX in processing schedules, by considering the maximum size of each room in scheduling,a nd by allowing the creation of a more dynamic sectioning scheme.